1997
DOI: 10.1143/jjap.36.2450
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Stabilized Pulsed Plasma via Suppression of Side-Band Modes

Abstract: The instabilities caused by the reflected rf power in a pulsed-plasma operation employing modulated rf power was studied. By suppressing the side-band modes in the frequency domain, the pulsed plasma became more stable and produced less reflected power. The mode-suppressed pulsed plasma showed almost the same plasma characteristics as the conventional step-function-modulated pulsed plasma. The mode-suppressed plasma was applied to etch a polysilicon pattern. The etched polysilicon profile showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Keller, Coultas, and Zhang'' have shown that the T^ of the negative-ion plasma over the wafer may be reduced by a factor of 3 or more compared to that of a conventional inductive plasma source. This means that etching would occur with a T^ of the order of 1 eV, or similar to that measured by Hahm et al [18], for 25 /us or more into the "off" part of a pulsed plasma. Visually such a plasma has the normal luminosity of an inductive plasma source below the dielectric window between the rf coil and the plasma.…”
Section: % Equipmentsupporting
confidence: 72%
See 2 more Smart Citations
“…Keller, Coultas, and Zhang'' have shown that the T^ of the negative-ion plasma over the wafer may be reduced by a factor of 3 or more compared to that of a conventional inductive plasma source. This means that etching would occur with a T^ of the order of 1 eV, or similar to that measured by Hahm et al [18], for 25 /us or more into the "off" part of a pulsed plasma. Visually such a plasma has the normal luminosity of an inductive plasma source below the dielectric window between the rf coil and the plasma.…”
Section: % Equipmentsupporting
confidence: 72%
“…During the off pulse, the electron temperature decreases to the order of 1 eV [18] through inelastic collisions and surface losses. Subsequently, the negative ion density increases relative to the electron density.…”
Section: % Equipmentmentioning
confidence: 99%
See 1 more Smart Citation